Leadership Competencies for Crisis Management : Insights from Retail Leaders During Pandemic Covid-19 - Victoria, Jonathan; Priscella, Ambrose (2022)
The retail sector is one of the most impacted during the COVID-19 pandemic, however, there is less understanding on the role of retail leaders in business sustainability during lockdown. This chapter presents the findings of nine in-depth interviews of small to mid-sized retail leaders in Sarawak, Malaysia on their business strategies and competencies that helped them overcome their challenges in their respective organizations. Findings from the study show the importance of crisis preparedness and crisis management for retailers. Competencies such as crisis planning and readiness, sense-making, strategic planning, problem solving and decision making, crisis communication, self-management, resiliency and learning ability are suggested as crucial to small retailers. From an HRD perspective, educators, policy makers and related trade associations need to work together with retailers to address retailer development needs.